Konflik Kepemilikan Pulau Marak Di Kecamatan Koto Xl Tarusan. Skripsi Program Studi Pendidikan Sosiologi, STKIP PGRI Sumatera Barat, Padang 2021. - Yulia Marlina Rinel fitlayeni, yuhelna (STKIP PGRI Sumatera Barat, 2021)
ABSTRACTSThis research is motivated by the concept of Agraria, Agraria is what is in the sea, on land such as forests and land or what is called natural resources. Natural resources are essentially used or utilized for the benefit of the community. Likewise, what happened in Nagari Sungai Pinang was due to too much power so that there was an inaccuracy in the issue of ownership of an island which was the trigger for the ownership conflict of Marak Island, Koto XI Tarusan District. The formulation of the research problem is the factor of ownership conflict in Marak Island in Koto Xl Tarusan District and how to manage Marak Island ownership conflict in Koto Xl Tarusan District and who are the actors involved in the ownership conflict of Marak Island in Koto Xl Tarusan District. The theory used in this research is conflict theory according to Randall Collins. The research approach used is a qualitative approach with descriptive research type. The types of data used in this study are primary data and secondary data. There were 7 informants involved in the conflict over ownership of Marak Island in Koto Xl Tarusa District. Data collection methods used in two ways, namely non-participant observation, in-depth interviews and document study. To achieve the validity of research data using triangulation techniques. Meanwhile, the data analysis units used were groups and individuals with data analysis by Miles and Huberman, namely data reduction, data presentation, and conclusion drawing. From the results of the study it can be concluded that there are several factors that support this conflict, such as the construction of homestay without permission, and the struggle for a physical tenure. In resolving this conflict, Wali Nagari, Pemuda, BAMUS as well as Ninik Mamak and Mr. Alex have made efforts to resolve this conflict through various processes and development carried out by PT Dempo since 15 April 2018. however this problem has not been resolved until now. Keywords: Conflict Cause, Actor involved, Conflict Resolution